ANALISIS PENERAPAN AKUNTANSI ASET TETAP BERBASIS AKRUAL DALAM PENYAJIAN LAPORAN KEUANGAN PADA PEMERINTAH DAERAH TIMUR KABUPATEN PAMEKASAN (Studi kasus pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Pamekasan) - Farhan Alif Wahyudi; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The government plays a role in improving financial information in the management of financial statements, so it is necessary to reform the financial statements as a basis. Fixed asset management is an effort to increase effectiveness, efficiency, and create more value in managing assets. The Pamekasan Regency Government in carrying out activities and implementation obtains an allocation of funds from the Regional Revenue and Expenditure Budget (APBD). Therefore, the Pamekasan Regency Government is obliged to prepare financial reports as a form of regional financial reports that have been obtained. The purpose of this study was to determine the application of accrual-based fixed asset accounting in financial statements based on PP No. 71 of 2010. This research method uses a qualitative approach with qualitative descriptive research. The results of this study indicate that the application of accrual-based fixed asset accounting in financial statements is in accordance with Government Regulation Number 71 of 2010, although it is still 80% with information system constrains, inadequate human resources, shortage of accounting experts and no application (SIMRAL) for support the system.Keywords : Effectiveness, Fixed Assets, Accruals, Financial Reports, PP No. 71 of 2010, Local Government.